"Blood, Bucks and Bias": Reliability and biasability of crime scene investigators' selection and prioritization of blood traces. Issue 2 (March 2023) - Lidén, Moa; Almazrouei, Mohammed A.
Highlights: Crime scene investigators' (CSIs) collection of traces is studied using heat maps. CSI's collection of blood is impacted by awareness of limited resources. Irrelevant contextual information indicating homicide or suicide biases trace collection. CSI's trace collection show both similarities and differences with that of novices. Abstract: When crime scene investigators (CSIs) encounter crime scenes with large volumes of blood, some selection and prioritization is often needed, and this will impact on what blood is and is not available for forensic analysis. What factors influence CSIs decision making process is largely unknown. This study examines the effects of awareness of limited resources and irrelevant contextual case information indicating either a homicide or a suicide on CSIs collection of blood traces. To this end, two scenario-based experiments with CSIs and novices were conducted. Overall, the results suggest that even when CSIs decisions are made under identical conditions, their trace selection varies both when it comes to numbers and locations. Furthermore, awareness of limited resources made CSIs collect fewer traces and their selections also varied following the contextual case information, showing similarities and differences with novices. Since blood traces can be used to establish both activity and identity the findings can have important implications for the subsequent investigation as well as trial.